Noise source identification - Danial, Mohamed (2014)
Noise source identification (NSI) techniques are used to optimise the noise emission from a wide range of products including vehicles, household goods and wind turbines. The goal of NSI is to identify the most important sub-sources on an object in terms of position, frequency content and sound power radiation. Ranking of the sub-sources can then be used to identify where design changes will most effectively improve the overall noise radiation. With a considerable number of techniques available, NVH engineers might have need of an overview to help select the most appropriate solution. This paper gives some guidelines to help the selection together with some practical applications of NSI techniques. Emphasis is placed on the useful frequency range and the resolution of the various methods.